Pengaruh Penggunaan TikTok terhadap Self-Esteem dan Body Dysmorphic Disorder pada Mahasiswa S1 Universitas Tanjungpura - Venny Venny; Agustina Arundina T.T; Desni Yuniarni (Fakultas Kedokteran, Universitas Andalas, 2026)
Background: Excessive use of social media can cause individuals to experience mental health problems such as anxiety disorders, depression, strees, eating behavior disorders and self-concept disorders. Therefore, this study focuses on the influence of the duration of tiktok social media use on self-esteem and tendency to body dysmorphic disorder that has not previously been studied. Objective: The aim is to determine the effect of TikTok usage duration on self-esteem and body dysmorphic disorder tendencies among undergraduate students of Tanjungpura University, class of 2020. Methods: This observational analytical study used a cross-sectional approach with 109 participants selected through purposive sampling. Variables were measured using the TikTok usage duration questionnaire, the Rosenberg Self-Esteem Scale, and a body dysmorphic disorder tendency questionnaire. Bivariate analysis was conducted using Spearman's rho correlation test. Results: Respondents had high TikTok usage, low self-esteem, and a low tendency toward body dysmorphic disorder. The Spearman's rho correlation showed no significant relationship between TikTok usage duration and self-esteem (0.722), but a significant correlation between TikTok usage duration and body dysmorphic disorder tendency (p = 0.000), and between self-esteem and body dysmorphic disorder tendency (p = 0.016). Conclusion: There is no significant influence of TikTok usage duration on self-esteem, but a significant influence exists between TikTok usage duration and body dysmorphic disorder tendency, as well as between body dysmorphic disorder tendency and self-esteem.